2007
DOI: 10.1186/1471-2482-7-2
|View full text |Cite
|
Sign up to set email alerts
|

The size criteria in minimally invasive video-assisted thyroidectomy

Abstract: BackgroundThyroid size is a very important criteria of MIVAT exclusion because the working space provided by the technique is limited.The aim of this work has been to verify the suitability of MIVAT and its applicability in clinical practice, not only in patients with a thyroid volume up to 25 ml but also in patients with a thyroid volume included from 25 to 50 ml.MethodsFrom January 2003 to February 2006, 33 patients have been selected for MIVAT. A completely gasless procedure was carried out through a centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…With the aim of moving the incision from the visible cervical regions to satisfy the higher cosmetic demands of patients, endoscopic techniques were adopted and modified for thyroid resection. This led to various extracervical approaches [6,25,[28][29][30][31]. More extensive dissection of subcutaneous layers was necessary, thereby increasing the risk of hematomas or severe scarring.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the aim of moving the incision from the visible cervical regions to satisfy the higher cosmetic demands of patients, endoscopic techniques were adopted and modified for thyroid resection. This led to various extracervical approaches [6,25,[28][29][30][31]. More extensive dissection of subcutaneous layers was necessary, thereby increasing the risk of hematomas or severe scarring.…”
Section: Discussionmentioning
confidence: 99%
“…Miccoli et al [27] standardized the technique for the transcollar approach with the use of endoscopic techniques [minimally invasive video-assisted thyroidectomy (MIVAT)] and worked with an incision length of 15-20 mm. The limiting factor in this approach is the size of the resected specimen [28]. Dysphagia due to scarring, especially in the platysmal muscle layer, may be problematic following the procedure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, the procedure generally is selected for patients with a thyroid volume less than 25 ml [24,25] or less than 30 ml [26][27][28], with a skin incision up to a maximum of 30 mm. Ruggieri et al [29] have reported that the procedure also can be performed smoothly in patients with a thyroid nodule of 25-50 ml in volume. As our experience with MIVAT increases, an expanded set of indications makes this procedure available to a broader population of patients.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding the indications of MIVAT, only a minority of patients with thyroid diseases affecting small glands are indicated for this kind of procedure; however recently, also thyroid gland volume, upper 25 ml [26], and patients with metastatic papillary thyroid carcinoma were included [27,28]. The number of patients undergoing MIVAT has significantly increased also because due to the progresses of ultrasonography, diagnosis is more and more early, and there is early diagnosis identifying the disease in the context of smaller thyroid gland.…”
Section: Discussionmentioning
confidence: 99%